2014
DOI: 10.1289/ehp.1307450
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Exposure and Depression among Male Private Pesticide Applicators in the Agricultural Health Study

Abstract: Background: Pesticide exposure may be positively associated with depression. Few previous studies have considered the episodic nature of depression or examined individual pesticides.Objective: We evaluated associations between pesticide exposure and depression among male private pesticide applicators in the Agricultural Health Study.Methods: We analyzed data for 10 pesticide classes and 50 specific pesticides used by 21,208 applicators enrolled in 1993–1997 who completed a follow-up telephone interview in 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
83
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 28 publications
10
83
2
2
Order By: Relevance
“…While the results we obtained from self-reported measures support the findings of and Beard et al (2014), the findings we obtained using diagnostic interviewing was less supportive. There are a number of potential reasons for the discrepancies between our findings and those previously reported.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…While the results we obtained from self-reported measures support the findings of and Beard et al (2014), the findings we obtained using diagnostic interviewing was less supportive. There are a number of potential reasons for the discrepancies between our findings and those previously reported.…”
Section: Discussioncontrasting
confidence: 96%
“…For example, evaluated the relationship between depression and pesticide exposure in 17,585 pesticide applicators enrolled in the AHS and found both acute high intensity and lower level exposures (in the absence of a history of acute poisoning) were associated with depression. More recently, Beard et al (2014) evaluated associations between mood disorder diagnosis and exposure to ten different classes of pesticides and fifty specific pesticides in 21,208 pesticide applicators, also in the AHS. They found that depression was associated with several specific pesticides, including OPs, even after controlling for other risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticide use raises significant concerns over impacts on health [2][3][4][5][6][7] and the environment [8][9][10][11][12]. Furthermore, we cannot address the challenges to sustainability posed by synthetic pesticides by simply switching to the application of natural pesticides, because the same concerns apply to them [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This simplificmtion of our food system contributes to climmte chmnge (Cmrlsson-Kmnymmm mnd Gonzmlez, 2009), rising pollution (Bemmn et ml., 2011;Morrissey et ml., 2015), biodiversity loss (Butler et ml., 2007;Lmndis et ml., 2008), mnd dmmmging lmnd use chmnges (Johnston, 2014;Wright mnd Wimberly, 2013) thmt mffect the sustminmbility, profitmbility mnd resilience of fmrms (Schipmnski et ml., 2016). Fmrmers experience the highest suicide rmte of mny profession in the United Stmtes, m rmte nemrly five-fold higher thmn the generml public (McIntosh et ml., 2016); the driving depression rmtes mre relmted to conventionml production prmctices (Bemrd et ml., 2014). Yet the scmle of our food production system provides opportunities for solving some of these plmnetmry scmle problems (Lml, 2004;Temgue et ml., 2016), but requires m systems-level shift in the vmlues mnd gomls of our food production system thmt de-prioritizes solely genermting high yields towmrd one thmt produces higher qumlity food while conserving our nmturml resource bmse.…”
mentioning
confidence: 99%